Émersion et apprentissage moteur: manifestations neurovégétatives lors de l`adaptation à une perturbation - Marie, C.; Maillot, P.; Hanneton, S. (Movement & Sport Sciences - Science & Motricité, 2018)
Learning gives rise to emersive phenomena. Neurovegetative correlates of learning have been extensively studied for cognitive tasks, in particular in training contexts, but much less for complex motor skill learning. We recorded the heart rate (HR) and the electrodermal response (EDR) of participants involved in the adaptation to a visuo-manual disturbance. Twenty one healthy right-handed participants were instructed to point to static targets with a graphic tablet. After a pre-test period, we introduced an unexpected rotation between the motor space (tablet) and the visual space (display), rotation then canceled for a post-test. During this task, four of the participants were exposed to a weak (5°) disturbance and the others to a strong (60°) disturbance. We searched for significant changes between successive blocks in the mean time profile of the HR and EDR. We found such significant changes not only on the perturbation onset and offset but also during the adaptation period in both signals in the 60° group. Particularly, we observed a significant drop in the HR and a significant increase in the EDR. These original results support the existence of a significant vegetative response during sensorimotor learning and encouraged us to investigate neurovegetative correlates of learning during more complex skills and to consider them in the framework of emersive phenomena.